Stratigraphic reconstruction of the Víti breccia at Krafla volcano (Iceland): insights into pre-eruptive conditions priming explosive eruptions in geothermal areas - Montanaro, Cristian; Mortensen, Anette Kærgaard; Weisenberger, Tobias B.; Dingwell, Donald B.; Scheu, Bettina (Bulletin of Volcanology, 2021)
Krafla central volcano in Iceland has experienced numerous basaltic fissure eruptions through its history, the most recent examples being the Mývatn (1724‒1729) and Krafla Fires (1975-1984). The Mývatn Fires opened with a steam-driven eruption that produced the Víti crater. A magmatic intrusion has been inferred as the trigger perturbing the geothermal field hosting Víti, but the cause(s) of the explosive response remain uncertain. Here, we present a detailed stratigraphic reconstruction of the breccia erupted from Víti crater, characterize the lithologies involved in the explosions, reconstruct the pre-eruptive setting, fingerprint the eruption trigger and source depth, and reveal the eruption mechanisms. Our results suggest that the Víti eruption can be classified as a magmatic-hydrothermal type and that it was a complex event with three eruption phases. The injection of rhyolite below a pre-existing convecting hydrothermal system likely triggered the Víti eruption. Heating and pressurization of shallow geothermal fluid initiated disruption of a scoria cone 'cap' via an initial series of small explosions involving a pre-existing altered weak zone, with ejection of fragments from at least 60-m depth. This event was superseded by larger, broader, and dominantly shallow explosions (~ 200 m depth) driven by decompression of hydrothermal fluids within highly porous, poorly compacted tuffaceous hyaloclastite. This second phase was triggered when pressurized fluids broke through the scoria cone complex 'cap'. At the same time, deep-rooted explosions (~ 1-km depth) began to feed the eruption with large inputs of fragmented rhyolitic juvenile and host rock from a deeper zone. Shallow explosions enlarging the crater dominated the final phase. Our results indicate that at Krafla, as in similar geological contexts, shallow and thin hyaloclastite sequences hosting hot geothermal fluids and capped by low-permeability lithologies (e.g. altered scoria cone complex and/or massive, thick lava flow sequence) are susceptible to ...